The transformative power of representation among youths: toward appreciating diversity and inclusion in Norway - Irene Bisasso Hoem; Marit Ursin; Carla Ramirez (Frontiers in Education)
In Norway, contemporary challenges linked to racism, discrimination, and social exclusion advocate for original approaches to enhance inclusion and appreciation of diversity. In this article, we draw on empirical material from two workshops with four youths from diverse backgrounds. The empirical material includes participant observation, group discussions, reflection logs, and informal dialogues. Using transformative learning theory, we explore whether and what kinds of learning processes occur when youths engage and interact in reflective activities aimed at appreciating diversity. Emphasizing the need to expand youths' existing frames of reference and points of view, the empirical material unveils the power of representation. The analysis suggests that although movies might have transformative potential, personal or peers' experiences make the movies “come alive” and more relatable. This increases the level of critical reflection and self-reflection among the youth participants, thus strengthening the transformative potential. Lastly, the analysis shows that both representation and context are crucial in activities seeking to enhance inclusion and appreciation of diversity.